-BIOCHEMICAL EFFECTS OF TRIGONELLA FOENUMGRAECUM L.SEEDS IN NORMAL AND ALLOXAN INDUCED DIABETIC RABBITS - Zainab A. Hassan; Ala Al-Deen H. Jawad (Basrah Journal of Veterinary Research)
This study was undertaken to investigate the effect of ethanolic extract of Trigonella foenum-graecum L. (fenugreek) seeds on blood glucose, total serum cholesterol and total serum protein in normal and alloxan induced diabetic rabbits. Twenty-four mature male rabbits (local breed) were randomly divided into four groups of equal number: (Control negative group (normal rabbits received 2 ml normal saline). Normal animals group treated orally with (200 mg /kg b.w.) alcoholic extract of fenugreek daily. Diabetic positive control group (induced diabetic rabbits received 2 ml normal saline). Diabetic group treated orally with (200 mg /kg b.w.) alcoholic extract of fenugreek daily. All group were deranched for six weeks. Diabetes was induced experimentally by single intravenous injection of alloxan monohydrate (100 mg/ kg b.w.).Estimation of blood glucose, total cholesterol and total protein was carried out weekly for all groups of the experiment. The results showed that alcoholic extract of T. foenum-graecum L. caused Significant decrease (P